2005
DOI: 10.1146/annurev.physiol.67.031103.154845
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tubule Albumin Transport

Abstract: Albumin is the most abundant protein in serum and contributes to the maintenance of oncotic pressure as well as to transport of hydrophobic molecules. Although albumin is a large anionic protein, it is not completely retained by the glomerular filtration barrier. In order to prevent proteinuria, albumin is reabsorbed along the proximal tubules by receptor-mediated endocytosis, which involves the binding proteins megalin and cubilin. Endocytosis depends on proper vesicle acidification. Disturbance of endosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
225
2
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(243 citation statements)
references
References 108 publications
7
225
2
9
Order By: Relevance
“…These data indicate that the mechanisms of signal transduction involved in AT 2 -mediated activation of PKB observed in our studies are very different from those reported for AT 1 -medited activation (18,19).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These data indicate that the mechanisms of signal transduction involved in AT 2 -mediated activation of PKB observed in our studies are very different from those reported for AT 1 -medited activation (18,19).…”
Section: Discussioncontrasting
confidence: 99%
“…To investigate which Ang II receptor is involved in the modulation of the albumin endocytosis, LLC-PK1 cells were treated with losartan and PD123319, specific antagonists for AT 1 and AT 2 receptors, respectively (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…b, c Hyaline droplet degeneration (black arrows) in the proximal convoluted tubule epithelium (b hematoxylin-eosin stain 9400, c periodic acid-methenamine silver stain 9400). d Electron microscopy showed more than 80 % foot process effacement (white arrows) with no electron-dense deposits As mentioned above, proteins that leak through the glomerulus combine with megalin and cubilin in the PTE and are taken into cells via endocytosis and reabsorbed in the blood after being disintegrated into amino acids in endosomes by lysosomal enzymes [8]. In addition, the possibility that the albumin taken into cells is collected via transcytosis has been reported.…”
Section: Discussionmentioning
confidence: 87%